A comprehensive review on thermochemical, and biochemical conversion methods of lignocellulosic biomass into valuable end product. (15th June 2023) - Awasthi, Mukesh Kumar; Sar, Taner; Gowd, Sarath C.; Rajendran, Karthik; Kumar, Vinay; Sarsaiya, Surendra; Li, Yue; Sindhu, Raveendran; Binod, Parameswaran; Zhang, Zengqiang; Pandey, Ashok; Taherzadeh, Mohammad J.
Graphical abstract: Highlights: Critical analysis of lignocellulose residue conversion was performed. Key technologies for fuel production from were discussed. Technical challenges in fuel cost reduction were presented. Future directions on the lignocellulosic-fuel process were proposed. Abstract: Lignocellulosic wastes have emerged as a potential feedstock in the last decades. There are multiple reasons for its abundance, easy availability, economic, and abundant sources. It can be used to produce several value-added products. Among them, fuel is considered one of the important requirements. Production of fuel from lignocellulosic biomass is a tricky business. The major reason for its failure is the low product yield. Therefore, high yield and low-cost are the two key parameters which need significant optimization. To achieve the target several newer technologies such as pyrolysis, hydrothermal liquefaction and gasification have emerged. These techniques are much more efficient than that of conventional acid or alkali. At the same time quality of the product is also improved. The focus of this review is to analyze the efficiency of chemical conversion of lignocellulosic residues into valuable fuels keeping in mind the cost-reduction strategies.